The Immune System GTPase GIMAP6 Interacts with the Atg8 Homologue GABARAPL2 and Is Recruited to Autophagosomes - Pascall, John C.; Rotondo, Sergio; Mukadam, Aamir S.; Oxley, David; Webster, Judith; Walker, Simon A.; Piron, Jerry; Carter, Christine; Ktistakis, Nicholas T.; Butcher, Geoffrey W. (PLOS ONE, 2013)
The GIMAPs (GTPases of the immunity-associated proteins) are a family of small GTPases expressed prominently in the immune systems of mammals and other vertebrates. In mammals, studies of mutant or genetically-modified rodents have indicated important roles for the GIMAP GTPases in the development and survival of lymphocytes. No clear picture has yet emerged, however, of the molecular mechanisms by which they perform their function(s). Using biotin tag-affinity purification we identified a major, and highly specific, interaction between the human cytosolic family member GIMAP6 and GABARAPL2, one of the mammalian homologues of the yeast autophagy protein Atg8. Chemical cross-linking studies performed on Jurkat T cells, which express both GIMAP6 and GABARAPL2 endogenously, indicated that the two proteins in these cells readily associate with one another in the cytosol under normal conditions. The GIMAP6-GABARAPL2 interaction was disrupted by deletion of the last 10 amino acids of GIMAP6. The N-terminal region of GIMAP6, however, which includes a putative Atg8-family interacting motif, was not required. Over-expression of GIMAP6 resulted in increased levels of endogenous GABARAPL2 in cells. After culture of cells in starvation medium, GIMAP6 was found to localise in punctate structures with both GABARAPL2 and the autophagosomal marker MAP1LC3B, indicating that GIMAP6 re-locates to autophagosomes on starvation. Consistent with this finding, we have demonstrated that starvation of Jurkat T cells results in the degradation of GIMAP6. Whilst these findings raise the possibility that the GIMAPs play roles in the regulation of autophagy, we have been unable to demonstrate an effect of GIMAP6 over-expression on autophagic flux.